1988
DOI: 10.1071/ea9880517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rates of flutriafol for control of blackleg of rapeseed

Abstract: The effect of flutriafol, applied at sowing as fungicide coated superphosphate, on the severity of blackleg disease of rapeseed was studied in the field. Fungicide rates from 50 to 200 g a.i./ha reduced disease severity and markedly increased yields. With blackleg resistant cultivars, economic yield responses were achieved even when disease severity was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Significant reductions in blackleg severity and increases in rapeseed yield were recently obtained in Australia with flutriafol applied at sowing as a coating on superphosphate fertilizer granules; no control was obtained with flutriafol as a seed dressing (Ballinger et al 1988a(Ballinger et al , 1988b. However, similar studies in Canada produced marginal and variable results (Xi et al , 1989Xi, Kutcher et al 1991).…”
Section: Controlmentioning
confidence: 87%
“…Significant reductions in blackleg severity and increases in rapeseed yield were recently obtained in Australia with flutriafol applied at sowing as a coating on superphosphate fertilizer granules; no control was obtained with flutriafol as a seed dressing (Ballinger et al 1988a(Ballinger et al , 1988b. However, similar studies in Canada produced marginal and variable results (Xi et al , 1989Xi, Kutcher et al 1991).…”
Section: Controlmentioning
confidence: 87%
“…However, these treatments do not protect plants grown in infested fields. Ballinger et al (1988) found that flutriafol applied as a fertilizer dressing on superphosphate granules significantly reduced the levels of stem canker in areas where the disease was prevalent. However, in western Canada, this fungicide had only limited efficacy (Xi et al 1989).…”
Section: Chemical Controlmentioning
confidence: 96%
“…Flutriafol is used as a fertiliser-amended fungicide as it causes toxicity if applied directly to the seed coat. Ballinger et al (1988) found that flutriafol increased plant height, decreased stem canker severity, increased plant survival, decreased leaf lesion severity and increased yields. Fluquinconazole is the predominant fungicide used by farmers for stem canker control due to the ease of application (seed dressing) and low cost.…”
Section: Chemical Control Practicesmentioning
confidence: 97%
“…Rainfall at sowing and minimum tillage cropping practices that leave infected crop residues on the soil surface combine to produce very severe early epidemics on seedlings. Technology transfer activities have emphasised the use of resistant cultivars, isolation of new crops from fields with crop residues (Barbetti et al, 2000;Khangura and Barbetti, 2001;Marcroft et al, 2004;Wherrett et al, 2004) and use of fungicides as seed or soil treatments (Ballinger et al, 1988;Khangura and Barbetti, 2002). Little emphasis has been placed on the use of fungicide spray treatments for stem canker control because of the low input -low yield production systems in many parts of Australia (Barbetti et al, 2000).…”
Section: Introductionmentioning
confidence: 97%